Correlation of ZnO surface morphology and sensing performance of EGFET nitrate sensor / A. B. Rosli ... [et al.] - Rosli, A. B.; Hashim, S. B.; Rahman, R. A.; Herman, S. H.; Abdullah, W. F. H.; Zulkifli, Z. (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2022)
Zinc oxide (ZnO) sensing electrode (SE) for extended gate field-effect transistor (EGFET) nitrate sensor was deposited on top of indium tin oxide (ITO) substrate using two different methods which were spin coating and chemical bath deposition (CBD) methods. To investigate the correlation between physical properties and sensing performance based on different growth methods, the deposited samples were characterized on its surface morphology using field emission scanning electron microscopy (FESEM). The ZnO sample deposited using spin coating showed an agglomerated structure while ZnO nanorods (ZnR) were observed on the ITO sample using the CBD method. Before the nitrate sensing measurement, the polyvinylpyrrolidone (PVP) polymer was deposited on top of ZnO samples for both methods at different concentrations of 2, 4 and 6 wt%. Both samples showed the ability as a SE for the EGFET nitrate sensor with 4 wt% PVP showed the optimum sensing behaviour. Based on the results obtained, the sensitivity of the ZnO SE using spin coating and ZnR by CBD method were 3.9 and 59.8 mV/dec, respectively, with the linearity 0.92919 and 0.98414, respectively. It was evident that nitrate sensing performance depended on the SE’s growth morphology. The high sensitivity of ZnR SE was related to nanorods structure that provides a high surface area and facilitates more contact between SE and nitrate solution for ion adsorptions. As a comparison, a sample without ZnO material with 4 wt% of PVP concentration was deposited and tested for nitrate sensing performance. The sensitivity and linearity of PVP sample were 20.60 mV/dec and 0.76601. It was proven that the ZnO material plays important role in increasing the nitrate sensing performance.